ELEKTRODELOKALISASI ZAT WARNA LIMBAH CAIR SARUNG TENUN SAMARINDA MENGGUNAKAN ELEKTRODA PbO2/Cu - Menono, Fera Friskaneke; Wirawan, Teguh; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2024)
Electrodecolorization of Sarung Tenun Samarinda liquid waste dyestuff using PbO2/Cu electrode has been conducted. This study aims to reduce the level of dyes in Sarung Tenun Samarinda liquid waste samples by electrodecolorization method using lead dioxide (PbO2) electrode as anode and Copper (Cu) as cathode. Electrodecolorization was carried out by varying the working potential, Na2SO4 electrolyte concentration, time, and dye concentration in order to obtain optimum conditions for dye decolorization by electrolysis process. The concentration of the dye was determined by calculating the absorbance data obtained from measurements using a UV-Vis spectrophotometer. The results showed that the optimum conditions of electrodecolorization on orange dyes using PbO2/Cu electrodes were a working potential of 10.5 volts, 0.2 M Na2SO4 electrolyte concentration and a time of 20 minutes. In green dyes, the optimum conditions are working potential of 10.5 volts, electrolyte concentration of Na2SO4 0.1 M and time for 15 minutes. The percentage of decolorization of the orange Sarung Tenun Samarinda liquid waste sample using the PbO2/Cu electrode was 100% and in the green Sarung Tenun Samarinda liquid waste sample was 100%.